2015
DOI: 10.1097/shk.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes After Severe Shock

Abstract: Background Severe shock is a life-threatening condition with very high short-term mortality. Whether the long-term outcomes among survivors of severe shock are similar to long-term outcomes of other critical illness survivors is unknown. We therefore sought to assess long-term survival and functional outcomes among 90-day survivors of severe shock and determine whether clinical predictors were associated with outcomes. Methods Seventy-six patients who were alive 90 days after severe shock (received ≥1 mcg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Among these articles, 52 unique studies evaluated return to work in previously employed ICU survivors (figure 1, table 1, online supplementary eTable 2). 4 5 13–63 These studies included 13 retrospective16 18 23 30 33 39 42 43 47 48 52 56 62 and 39 prospective4 5 13–15 17 19–22 24–28 30–32 34–38 40 41 44–46 49–51 53–55 57–61 63 cohort studies, of which three were longitudinal follow-up within a randomised trial 4 37 59. Eleven (21%) studies included more than one follow-up time point after discharge 4 5 26 28 29 34 37 45 49 51 55 62.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these articles, 52 unique studies evaluated return to work in previously employed ICU survivors (figure 1, table 1, online supplementary eTable 2). 4 5 13–63 These studies included 13 retrospective16 18 23 30 33 39 42 43 47 48 52 56 62 and 39 prospective4 5 13–15 17 19–22 24–28 30–32 34–38 40 41 44–46 49–51 53–55 57–61 63 cohort studies, of which three were longitudinal follow-up within a randomised trial 4 37 59. Eleven (21%) studies included more than one follow-up time point after discharge 4 5 26 28 29 34 37 45 49 51 55 62.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies conducted employment assessments during either the first (2000–2004) or second (2008–2010) global economic downturns occurring during the publication period 4 32 36 46–48 50–52 55 63 64. Twenty-eight (54%) studies were conducted in Europe,15 17 18 20 22 25–27 30–36 38–42 44 48–51 58 62 63 14 (27%) in North America,4 5 13 14 16 19 23 24 28 29 37 45 52 55 60 8 (15%) in Australia/New Zealand21 43 46 47 53 54 59 61 and 2 (4%) in Asia 56 57. Nine studies (17%) evaluated return to work in survivors of ARDS 4 5 19 24 39 45 47 57 63.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICU survivors have high rates of mortality and increased health care utilization following discharge [213]. The rise in survivorship has created a burgeoning population suffering from long-term consequences of critical care [1318], including cognitive impairment [1823], anxiety [1618], depression [13, 1518], post-traumatic stress disorder [1318, 24], decreased quality of life [9, 12, 2529], and physical disability [17, 20, 30, 31]. This constellation of problems is now known as PICS, a condition of new or worsening dysfunction in key domains such as cognition and physical function that persists beyond the inciting critical illness [32].…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study on the long-term outcome of severe shock revealed that most patients who survived a 90-day period also survived 3 years or more (6). Thirty-nine percent had anxiety, and 19% had depression symptoms.…”
mentioning
confidence: 99%